A Simple Theory of Argument Schemes - Goddu, Geoff C. (Informal Logic, 2021)
While there has been in depth discussion of many particular argumentation schemes, some lament that there is little to no theory underpinning the notion of an argumentation scheme. Here I shall argue against the utility of argument schemes, at least as a fundamental part of a complete theory of arguments. I shall also present and defend a minimalist theory of their nature—a scheme is just a set of proposition expressions and propositional functions. While simple, the theory contravenes several typical desiderata of argumentation schemes such as (i) aiding in the identification of enthymemes and (ii) keeping arguments constrained to a manageable taxonomy. So much the worse for the desiderata. Instead, I shall recommend focusing less on schemes and more on the component propositional functions.